Transdermal Nicotine Application Attenuates Cardiac Dysfunction after Severe Thermal Injury. (28th July 2015) - Claassen, Leif; Papst, Stephan; Reimers, Kerstin; Stukenborg-Colsman, Christina; Steinstraesser, Lars; Vogt, Peter M.; Kraft, Theresia; Niederbichler, Andreas D.
Abstract : Background . Severe burn trauma leads to an immediate and strong inflammatory response inciting cardiac dysfunction that is associated with high morbidity and mortality. The aim of this study was to determine whether transdermal application of nicotine could influence the burn-induced cardiac dysfunction via its known immunomodulatory effects. Material and Methods . A standardized rat burn model was used in 35 male Sprague Dawley rats. The experimental animals were divided into a control group, a burn trauma group, a burn trauma group with additional nicotine treatment, and a sham group with five experimental animals per group. The latter two groups received nicotine administration. Using microtip catheterization, functional parameters of the heart were assessed 12 or 24 hours after infliction of burn trauma. Results . Burn trauma led to significantly decreased blood pressure (BP) values whereas nicotine administration normalized BP. As expected, burn trauma also induced a significant deterioration of myocardial contractility and relaxation parameters. After application of nicotine these adverse effects were attenuated. Conclusion . The present study showed that transdermal nicotine administration has normalizing effects on burn-induced myocardial dysfunction parameters. Further research is warranted to gain insight in molecular mechanisms and pathways and to evaluate potential treatment options in humans.